2015
DOI: 10.1158/0008-5472.can-15-0125
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Prostaglandin E2–EP2 Signals in the Colon Tumor Microenvironment That Amplify Inflammation and Tumor Growth

Abstract: Inflammation in the colon contributes significantly to colorectal cancer development. While aspirin reduces the colorectal cancer risk, its action mechanism, especially in inflammation in tumor microenvironment, still remains obscure. Here, we examined this issue by subjecting mice deficient in each prostaglandin (PG) receptor to colitis-associated cancer model. Deficiency of PGE receptor subtype EP2 selectively reduced, and deficiency of EP1 and EP3 enhanced, the tumor formation. EP2 is expressed in infiltrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(115 citation statements)
references
References 50 publications
(53 reference statements)
4
105
0
Order By: Relevance
“…For instance, prostaglandins are highly elevated in the tumor stroma of many types of cancer, including breast cancer (45, 5355). We found nuclear accumulation of phosphorylated CREB1 in the tumor vascular endothelium of human breast cancer, indicating chronic activation of cAMP signaling in these vessels.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, prostaglandins are highly elevated in the tumor stroma of many types of cancer, including breast cancer (45, 5355). We found nuclear accumulation of phosphorylated CREB1 in the tumor vascular endothelium of human breast cancer, indicating chronic activation of cAMP signaling in these vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Ma et al . found extensive neutrophil infiltration in association with tumour development in the colon in the AOM/DSS‐induced colitis‐associated colorectal cancer model and reported that PGE 2 was involved in this sustained neutrophil accumulation (Ma et al ., ). Infiltrating neutrophils highly express EP 2 receptors and an EP 2 receptors agonist and TNF‐α synergistically induced the expression of various inflammation‐related genes in vitro in primary cultured neutrophils, which included COX‐2, IL‐6 and CXCL1, through NF‐κB.…”
Section: Pg‐cytokine Crosstalk In Myeloid and Stromal Cell‐mediated Cmentioning
confidence: 97%
“…Infiltrating neutrophils highly express EP 2 receptors and an EP 2 receptors agonist and TNF‐α synergistically induced the expression of various inflammation‐related genes in vitro in primary cultured neutrophils, which included COX‐2, IL‐6 and CXCL1, through NF‐κB. A deficiency in EP 2 receptors or EP 2 antagonism abolished neutrophil infiltration, suppressed the expression of inflammatory genes including CXCL1 and decreased the number of colon tumours (Ma et al ., ). These findings are consistent with the preceding study by Katoh et al .…”
Section: Pg‐cytokine Crosstalk In Myeloid and Stromal Cell‐mediated Cmentioning
confidence: 97%
“…It was also found that disease-specific mortality in colorectal cancer showed a negative correlation with EP2 receptor expression (5,6). Moreover, several studies have displayed that EP2-knockout mice have reduced tumor growth compared with tumors in wild-type mice (7)(8)(9)(10)(11). Therefore, we speculate that the differences in gene expression among tumors growing on EP2-knockout mice versus tumors growing on wild-type mice may indicate important signaling between the tumor and stroma tissue, which subsequently determines tumor growth and progression.…”
Section: Introductionmentioning
confidence: 99%